PENERAPAN PENDEKATAN PROBLEM POSING UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK SISWA KELAS IV SD NEGERI 0710 ALIAGA IV KECAMATAN HUTARAJA TINGGI - Rinja Efendi; Nauli Tama Sari; Bengsan Bengsan (STKIP ROKANIA, 2022)
This study aims to improve student thematic learning outcomes through the application of the Problem Posing approach. Preliminary data on student learning outcomes are still low, as evidenced by 36 students only 25% of students who complete and 75% of students who do not complete below the KKM 75 are determined by the school. This research is classroom action conducted in 2 cycles, consisting of planning, implementation, observation and reflection. The subjects of this study were fourth grade students of SD Negeri 0710 Aliaga IV, Hutajara Tinggi District. Data collection techniques using tests and observations. The research instrument used observation sheets and learning outcomes test questions. The results showed that before the implementation of the Problem Posing approach in thematic learning, 25% were completed, 75% were incomplete. After doing research on learning outcomes in the first cycle of meeting 1 obtained 63.89% of students completed, in the first cycle of meeting 2 increased to 69.44% of students who completed, in the second cycle of meeting 1 obtained 88.89% of students completed and in the second cycle of meetings 2 increased to 88.89% of students completed. Research on the application of the Problem Posing approach to Improve Thematic Learning Outcomes of Grade IV Students at SD Negeri 0710 Aliaga IV, Hutaraja Tinggi District